2021
DOI: 10.3390/cancers13133308
|View full text |Cite
|
Sign up to set email alerts
|

DeepRePath: Identifying the Prognostic Features of Early-Stage Lung Adenocarcinoma Using Multi-Scale Pathology Images and Deep Convolutional Neural Networks

Abstract: The prognosis of patients with lung adenocarcinoma (LUAD), especially early-stage LUAD, is dependent on clinicopathological features. However, its predictive utility is limited. In this study, we developed and trained a DeepRePath model based on a deep convolutional neural network (CNN) using multi-scale pathology images to predict the prognosis of patients with early-stage LUAD. DeepRePath was pre-trained with 1067 hematoxylin and eosin-stained whole-slide images of LUAD from the Cancer Genome Atlas. DeepRePa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 37 publications
2
25
0
1
Order By: Relevance
“…However, in a previous study, 30% of patients at those stages showed disease recurrence ( 6 , 32 ). Actually, clinicians have some difficulty deciding on chemotherapy to prevent recurrence in stage I patients ( 6 ). We suggest that TB may help identify patients at high risk of recurrence and offer them adjuvant chemotherapy, especially in cases where they otherwise may not receive necessary treatment.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, in a previous study, 30% of patients at those stages showed disease recurrence ( 6 , 32 ). Actually, clinicians have some difficulty deciding on chemotherapy to prevent recurrence in stage I patients ( 6 ). We suggest that TB may help identify patients at high risk of recurrence and offer them adjuvant chemotherapy, especially in cases where they otherwise may not receive necessary treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, adjuvant chemotherapy for lung cancer is limited to patients with lung cancer beyond stage I. However, in a previous study, 30% of patients at those stages showed disease recurrence ( 6 , 32 ). Actually, clinicians have some difficulty deciding on chemotherapy to prevent recurrence in stage I patients ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mutations apparently lead to morphological changes which are detectable by artificial intelligence techniques, especially convolutional neural networks (CNNs). Such works have laid the ground for the rising number of studies investigating AI for the prediction of oncological outcomes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%